Mortality associated with cysticercosis in a historical cohort from Britain - Singh, Gagandeep; Chiodini, Peter; Sander, Josemir W. (Arquivos de Neuro-Psiquiatria, 2022)
Background: The burden of premature mortality associated with human cysticercosis is largely ignored mainly due to poor record-keeping in Taenia solium endemic regions. Objective: To document mortality and survival characteristics of an historical cohort with cysticercosis. Methods: The years of onset of symptoms and death untill 1957 were extracted from published reports of a British military cohort (n=450) examined in London in the early twentieth century. Data were entered into a Kaplan Meier survival analysis with the presence (or absence) of clinical manifestations as independent variables, which were then fitted into a Cox proportional hazards model to determine their significance. Results: Cysticercosis was responsible for 24 (52.2%) of 46 deaths in the first 15 years of follow-up in comparison to 7 (19.4%) of 36 deaths in the 20-40 years of follow-up period. In the univariate and Cox analyses, intracranial hypertension (hazard ratio [HR]: 8.26; CI: 4.71, 14.49), ocular cysticercosis (HR: 6.60; CI: 3.04, 14.33), and mental disorder (HR: 3.98; CI: 2.22, 7.13) but not epilepsy (HR: 0.66; CI: 0.20, 2.18) were associated with mortality. Over half of all deaths in the first 15 years of follow-up were attributed to cysticercosis. Conclusions: Several deaths occurred early after acquiring cysticercotic infection. Intracranial hypertension, ocular cysticercosis, and mental disorder but not epilepsy were predictors of mortality in this cohort.
Keywords: Taenia solium; Epilepsy; Intracranial Hypertension; Survival; Mortality